2017
DOI: 10.1007/s00380-017-0950-2
|View full text |Cite|
|
Sign up to set email alerts
|

Effects on bone metabolism markers and arterial stiffness by switching to rivaroxaban from warfarin in patients with atrial fibrillation

Abstract: In recent years, direct oral anticoagulants (DOACs) of dabigatran, rivaroxaban, apixaban, edoxaban, which are all alternatives to warfarin, have been released. The use of DOACs is becoming more widespread in the clinical management of thrombotic stroke risk in patients with atrial fibrillation (AF). In large-scale clinical trials of each drug, DOACs were reported to inhibit intracranial hemorrhage, stroke, and death compared to warfarin. Warfarin is an endogenous vitamin K antagonist; therefore, patients who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 30 publications
1
20
0
6
Order By: Relevance
“…37 Certain studies corroborate the fact that replacing VKAs with NOACs would improve the bone markers. 38 Likewise, our data support the notion that the continuous use of acenocoumarol increases osteoporosis risk as an adverse reaction. Some publications have focused on the possible usefulness of modifying the anticoagulant treatment in patients at risk for osteoporosis.…”
Section: Discussionsupporting
confidence: 82%
“…37 Certain studies corroborate the fact that replacing VKAs with NOACs would improve the bone markers. 38 Likewise, our data support the notion that the continuous use of acenocoumarol increases osteoporosis risk as an adverse reaction. Some publications have focused on the possible usefulness of modifying the anticoagulant treatment in patients at risk for osteoporosis.…”
Section: Discussionsupporting
confidence: 82%
“…An interesting study by Namba et al (75) examined the effect on bone metabolism markers and atherosclerosis measures in patients with atrial fibrillation when switching from warfarin (a vitamin K antagonist) to rivaroxaban (75). This study found ucOC concentrations to decrease after 6 months of rivaroxaban treatment as vitamin K was no longer prohibited.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, the vast majority of papers (52 of 63 papers) described crosssectional associations of sub-ECM level factors with PWV (Tables 1, 2, 3, and 4). A small number of intervention studies (11 of 63 studies) addressed changes in arterial stiffness through modulation of ECM integrity (1,61,68,94,143) or smooth muscle tone (4,7,10,41,116,136). Only a handful (3 of 63 studies) used a modeling approach to quantitatively interpret these changes at the level of elastin, collagen, and ECM (42,64,125).…”
Section: Overall Summary Of Clinical-epidemiological Review Findingsmentioning
confidence: 99%